2017
DOI: 10.1002/nau.23193
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional translabial ultrasound assessment of urethral supports and the urethral sphincter complex in stress urinary incontinence

Abstract: Ultrasound evaluation of urethral supports does not discriminate between continent and incontinent women. However, the length of the USC at rest was shorter and urethral mobility was higher in incontinent women. Neurourol. Urodynam. 9999:XX-XX, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In a study using three‐dimensional translabial ultrasound, Garriga et. al did not find significant differences in urethral fascial support between women with and without SUI 19 . On the other hand, several MRI studies have revealed greater prevalence in distortion and defect of the “periurethral ligament” (also referred to as the pubovisceral muscle) and “paravaginal ligament” (also referred to as the endopelvic fascia) among women with SUI compared to women without SUI 9,10 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In a study using three‐dimensional translabial ultrasound, Garriga et. al did not find significant differences in urethral fascial support between women with and without SUI 19 . On the other hand, several MRI studies have revealed greater prevalence in distortion and defect of the “periurethral ligament” (also referred to as the pubovisceral muscle) and “paravaginal ligament” (also referred to as the endopelvic fascia) among women with SUI compared to women without SUI 9,10 .…”
Section: Discussionmentioning
confidence: 91%
“…5,17 Prior studies have investigated differences in urethral morphology on ultrasound and MRI in women with and without SUI. 9,10,16,16,18,19 In a study using three-dimensional translabial ultrasound, Garriga et. al did not find significant differences in urethral fascial support between women with and without SUI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study may be limited because control group data was not collected (15,29,30). Besides, all the stored 4D pelvic floor ultrasound data sets are stable and all the examinations lack duplication, so the analysis of these data sets might not truly be reflective of the clinical practice and the achieved perfect consistency (25).…”
Section: Discussionmentioning
confidence: 98%